SELF IDENTITY MANAGEMENT UMKM DALAM CYBERSPACE : PERSPECTIF PASCA TRANSFORMASI DIGITAL UMKM DI KAWASAN DESTINASI WISATA GEOPARK CILEUTUH - Deri Firmansyah; Asep Achamd Rifa’i; Asep Suryana; A Idun Suwarna (Bajang Institute, 2021)
The ability of micro-enterprises (Mi) and small-enterprises (Se) to carry out digital transformation using social media cyberspace as their cyberpreneur in cyberspace is not supported by the ability to manage their identity, which triggers a lack of awareness of signs of account theft as well as data and identity obscuration. they. The purpose of community service activities is to provide training related to increasing digital literacy for self-identity management for Mi and Se actors who have carried out digital transformation to avoid cyber crime. The implementation method is carried out through the direct observation and training stages. This activity offers mentoring and training as solutions and approaches that are considered relevant. With this training they have additional knowledge and skills in the digital field that can increase understanding in managing self-identity, data and information in social media cyberspace, and can encourage more insight in marketing their products while promoting the tourist attraction of Geopark Cileutuh virtually, even more daring to try. enter a more global e-commerce platform and marketplace.